Kajian Struktural, Sosial, Budaya, Agama, Dan Nilai Pendidikan Dalam Novel Harimau! Harimau! Karya Mochtar Lubis - Ghufroni Ghufroni (Jurnal Ilmiah SEMANTIKA, 2020)
This study aims to describe: 1) the structure of the Tiger novel! Tiger! 2) The social background of the Tiger novel! Tiger! 3) Cultural background of the Tiger novel! Tiger! 4) Religious background, and 5) Educational value in the Tiger novel! Tiger!. This study uses a qualitative descriptive method with a sociological approach to literature. Sources of research data consisted of objective data sources in the form of text data, genetic data sources in the form of author biographies and informants by conducting interviews with observers and literature lovers. Based on the results of the analysis of this study it can be concluded as follows: 1) The structure of the novel "Tiger! Tiger!" Mochtar Lubis's work with Themes, no matter how small the crime that is stored, will be exposed as well. Mandate: Life is most important believe in God and yourself. Language style uses personification. The plot / plot of this novel uses a plot / plot forward and backward. Characterization / Characteristics of good and evil doers. The setting / setting was built in the middle of a wilderness. 2) Social background is Belief in customs, superstitious ties, marriage, about leadership, religious life, and social harmony 3) Cultural background is a matter of marriage that is not based on genuine love and affection 4) Religious background is upholding religious value to repent before dying 5) Educational value of the Tiger novel! Tiger! Is the value of strong friendship and high tolerance.Abstract is written in English in maximum of 200 words in italics with Times New Roman 11 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied, the method how to solve the problem and the result(s). Abstract preferably end with a comment about the importance of the results or conclusions briefly